Klinische Sportmedizin - Hazzaa Walaa Eldin A; 2; Mattes K (Dynamic Media Sales Verlag, 2018)
Background: Changes in foot strikepattern by local muscle fatigue can increase the rate of injury in running. The aim of this study was to investigate the influence of foot strikepattern and local muscle fatigue of the plantar flexors and dorsiflexors on plantar pressure distribution while running barefoot on a treadmill at three different speeds. Methods: The study included 52 male voluntary forefoot vs. rearfoot runners of similar age and body mass. Each group completed two tests, with an interval of 3-7 days. The fatigue protocol included the isometric maximum force test consisting of two sets with a maximum contraction and the isokinetic endurance test consisting of ten sets of six concentric contractions (10s set break, =60/s). Variance analysis with repeated measurements was used to check the differences. Results: The fatigue protocol reduces the efficiency of the plantar flexors and dorsiflexors, which perform different foot strikefunctions during running. As expected, the plantar pressure distribution under the foot was different depending on the foot strikepattern and local muscle fatigue. The pressure maxima was reduced under the exposed foot regions after fatigue, that means the maximum pressure is reduced after local muscle fatigue.Conclusion: For injury prevention, the foot strikepattern should be varied to relieve in particular the foot area under the heel and the forefoot. In the case of forefoot strikers, checks should be made as to whether they are habitual forefoot strikers.KEY WORDS: Forefoot, Rear Foot, Isometric Strength Test, Isokinetic Endurance Test